False friend : a novel - Grant, Andrew, 1968- (Ballantine Books, 2017)
"Detective Devereaux is hot on the heels of an arsonist--one who is targeting local schools. When long-buried bones are uncovered at the site of a fire, a deadly secret is exposed and a devastating past threatens to be revealed. Meanwhile, an enemy is determined to expose the darkest corners of Devereaux's past"--